2017
DOI: 10.1115/1.4038153
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation for Radiative Transfer in a High-Pressure Industrial Gas Turbine Combustion Chamber

Abstract: Radiative heat transfer is studied numerically for reacting swirling flow in an industrial gas turbine burner operating at a pressure of 15 bar. The reacting field characteristics are computed by Reynolds-averaged Navier-Stokes (RANS) equations using the kmodel with the partially stirred reactor (PaSR) combustion model. The GRI-Mech 2.11 mechanism, which includes nitrogen chemistry, is used to demonstrate the ability of reducing NO x emissions of the combustion system. A photon Monte Carlo (PMC) method coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Early coupled simulations using Reynolds average Navier-Stokes (RANS) include the studies of diffusion jet flames of Tessé et al [33] who pointed out the important role of soot particles in global radiative loss; and the work of Li and Modest [34] in which was found that TRI reduces the total drop in flame peak temperature caused by radiative heat losses. Additionally, a recent RANS coupled simulation in a high-pressure gas turbine combustion chamber was reported by Ren et al [35].…”
Section: Introductionmentioning
confidence: 99%
“…Early coupled simulations using Reynolds average Navier-Stokes (RANS) include the studies of diffusion jet flames of Tessé et al [33] who pointed out the important role of soot particles in global radiative loss; and the work of Li and Modest [34] in which was found that TRI reduces the total drop in flame peak temperature caused by radiative heat losses. Additionally, a recent RANS coupled simulation in a high-pressure gas turbine combustion chamber was reported by Ren et al [35].…”
Section: Introductionmentioning
confidence: 99%
“…The LSQCURVEFIT function in Matlab has been used for the curve fitting of absorption coefficients and weighting factor with different pressures, mole ratios, and temperatures. The absorption coefficient depends on pressure P, mole ratio MR, and normalized temperature defined as T/T ref , as shown in Equation (6).…”
Section: Pressurized Wsgg Modelmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) simulation depends on reliable models, [5][6][7][8][9] which is of great importance for the study of pressurized oxy-fuel combustion. Due to the elevated pressure and CO 2 -rich environments, many submodels based on atmospheric combustion development are no longer suitable for pressurized oxy-fuel combustion, especially for radiative property models.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the combustion in gasifiers [7] or gas turbine combustion chambers [8], the reaction pressure is much higher than atmospheric pressure. For example, the Bioliq gasifier [9] produced syngas from a biomass feedstock at a pressure of 40 atm and an industrial gas turbine burner [10] with 5 MW output operated at a pressure of 15 atm. Numerical simulations of such a gasifier or gas turbine require radiative parameters of participating medium at elevated pressures.…”
Section: Introductionmentioning
confidence: 99%